2013
DOI: 10.1016/j.matbio.2013.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of interleukin-1α and transforming growth factor-β1 on modulation of human cardiac fibroblast function

Abstract: A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT AbstractDuring cardiac remodeling, cardiac fibroblasts (CF) are influenced by increased levels of interleukin-1α (IL-1α) and transforming growth factor-β1 (TGFβ1). The present study investigated the interaction between these two important cytokines on function of human CF and their differentiation to myofibroblasts (CMF). CF were isolated from human atrial appendage and exposed to IL-1α and/or TGFβ1 (both 0.1 ng/ml). mRNA expression levels of selected gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 29 publications
4
20
0
2
Order By: Relevance
“…h, in agreement with our recent report [30], but there was no difference between T2DM and ND CF (Fig. 3D).…”
Section: Influence Of T2dm On Basal and Il-1 Induced Gene Expressionsupporting
confidence: 93%
See 1 more Smart Citation
“…h, in agreement with our recent report [30], but there was no difference between T2DM and ND CF (Fig. 3D).…”
Section: Influence Of T2dm On Basal and Il-1 Induced Gene Expressionsupporting
confidence: 93%
“…Specifically, we investigated expression of the proinflammatory cytokines IL1 , IL6 and IL8, the genes that we have previously studied in this cell type [23,[28][29][30].…”
Section: Influence Of T2dm On Basal and Il-1 Induced Gene Expressionmentioning
confidence: 99%
“…IL-1α/β, TGF-β1, and fibronectin) [44]. The Turner lab has demonstrated that stimulating human cardiac fibroblasts to IL-1α upregulates the expression of IL-6, IL-8, MMP-3, and collagen III and downregulates α-SMA and CTGF [81]. In comparison, TGF-β1 significantly elevates α-SMA, CTGF, collagen1α1 and collagen3α1 expression, with minor effects on IL-6, IL-8, and MMP-3.…”
Section: Knowledge Gap 3 Computational Models Simulating Post-mi LV mentioning
confidence: 99%
“…Within this range and in line with previous in vitro observations of CFs behavior (Ugolini et al, 2016), we selected 2% strain as indicative of reduced contractility and 8% strain as representative of full myocardial contractility. These environmental changes and the following initial cellular responses happen in a timeframe of hours, as shown in vitro (van Nieuwenhoven et al, 2013; Turner et al, 2007, 2009) as well as in vivo (Guillén et al, 1995; Morishita et al, 2015). We thus performed experiments lasting 24 hr and evaluated the main early aspects that govern fibrotic responses in the injured myocardium: ECM remodeling, with stainings for collagen I and quantifications of MMP expression; proliferation of CFs, with analyses of mitotic cells, Hippo pathway signaling and mitogenic PDGF (platelet-derived growth factor) expression; secretion of inflammatory and pro-fibrotic cytokines in CF supernatants; myofibroblast differentiation, through stainings for αSMA (α-smooth muscle actin).…”
Section: Introductionmentioning
confidence: 99%